Efektivitas Proses Mediasi Dalam Perkara Perceraian Di Pengadilan Agama Jakarta Timur - Nur Lina Afifah Litti; Rajiv Nazry Faizullah Sina Gula; M. Hapis Ray; Fahrurazi Fahrurazi; Oneng Nurul Bariyah; Siti Rohmah (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
Reconciling parties who are litigating in Court is not an easy matter. This can be caused by the lack of availability of legal institutions that can assist parties in choosing the right method for dispute resolution, the lack of public understanding of the importance of implementing mediation in the Religious Courts, and the concept of hakam (peacemaker) which has not been applied by the Court. The purpose of this study was to determine the effectiveness of the mediation process in divorce cases at the East Jakarta Religious Court. The method used in this research is qualitative. While the approach used is descriptive- analysis. By systematically describing the facts and characteristics of the object and subject under study precisely. The data collection technique uses direct observation to the object of research to see up close in order to obtain information about the situation and conditions of the East Jakarta Religious Court, then interviewing Judges and Mediators, and finally Documentation. The results showed that the effectiveness of the mediation process in divorce cases at the East Jakarta Religious Court was still ineffective. From the data obtained, the number of cases that have been successfully mediated in the past 3 years is less than 15%.